Biocontrol efficacy of Bacillus licheniformis and Bacillus amyloliquefaciens against rice pathogens - Mohsin Tariq; Mehvish Zahoor; Tahira Yasmeen; Tahir Naqqash; Muhammad Abdul Rehman Rashid; Muhammad Abdullah; Abdul Rafay Rafiq; Marriam Zafar; Iqra Irfan; Ijaz Rasul (PeerJ)
Biocontrol is a cost-effective and eco-friendly approach to control plant pathogens using natural enemies. Antagonistic microorganisms or their derivatives specifically target the plant pathogens while minimizing the harm to non-target organisms. Bacterial blight and brown spot are the major rice diseases caused by Xanthomonas oryzae pv. oryzae (Xoo) and Bipolaris oryzae (Bo), respectively. This study was conducted to assess the plant growth-promoting potential and biocontrol activity of root-associated bacteria against the rice pathogens, Xoo and Bo. A total of 98 bacteria were isolated from rice roots and characterized for plant growth-promoting properties including phosphate solubilization, indole-3-acetic acid production, nitrogen fixation and biofilm formation. Based on these properties, 36 bacteria were selected and tested for biocontrol potential against rice pathogens via co-culturing antagonism assay. LE7 exhibited the maximum inhibition of 79%, while FR8, PE2, LE7, LR22 and LR28 also significantly reduced the growth of Xoo. Likewise, FR2, LR22, LR35 and LE7 significantly inhibited the growth of Bo, in which LR22 exhibited the maximum inhibition of 81%. Under controlled-conditions, LE7 and LR22 significantly reduced the disease incidence of Xoo and Bo, respectively, and improved the growth of rice. Full-length 16S rRNA gene sequencing of most potential bacterial isolates, LE7 and LR22, revealed their maximum identity with Bacillus amyloliquefaciens and Bacillus licheniformis, respectively. Application of Bacillus spp. as biocontrol agent represents enormous potential in rice farming. The most promising bacterial isolates could be used as bioinoculants for rice disease management and improved production in a sustainable manner.